Correlation Analysis of Price, Location and Facilities Relationships To Economic Visitor Traffic One Home Farm - Pratiwi, Ratih; Merdekawati, Eka; Rosiana, Nia (AIBPM Publisher, 2023)
An economy that is oriented towards a system of feasibility based on security and convenience is the basis for economic actors to compete with each other to provide the best options for partners. This system involves the standardization value shown. Therefore, geographical/regional factors must be carried out and studied more broadly, on the impact on the related industrial sector. One of the economic industrial sectors that is still active in the agricultural sector in the Bogor area is One Home Farm. the purpose of this study is to determine the level of correlation between the variables price, location, and facilities whether they have enough effect on the intention to visit One Home Farm. The flow of this research method uses a descriptive quantitative approach, in which the results of calculations and processing of SPSS data are translated and studied further with the support of a literature review. Based on the simultaneous test results obtained F count = 8.981, with a p value of 0.000 <0.05, in accordance with the above conditions means the hypothesis states that simultaneously the independent variables (price, location and facilities) have a significant effect on the decision to visit One Home Farm. The results of the study also show the percentage value of the visiting decision variable by the independent variable (coefficient of determination) which is indicated by the value. Adjusted R Square (R2) of 0.406. in this case it can be interpreted that the decision to visit can be explained by price, location and facilities of 40.6% while the remaining 49.4% is explained by other variables not examined in this study.